Analisis kualitas pelayanan bus pariwisata dengan metode service quality dan importance performance analysis - Eka Indah Yulistyari; Chotibul Umam; M. Reiza Fachrozy (Universitas Mercu Buana, 2019)
PO. Saztro Holidays is one of the bus transportation services companies in the Serang area that focuses on tourism routes. The purpose of this study is to know the quality of tourism bus services through customer satisfaction and complaints, besides as knowing the importance of priority attributes to be repaired. The methods of collecting data using a questionnaire involving 30 respondents to tourism bus consumers. This study uses the SERVQUAL method (reliability, responsiveness, assurance, empathy, tangible) and Importance Performance Analysis (IPA). The results of the study using the SERVQUAL method obtained an overall gap value of -0.852, which states that the services provided by PO. Saztro Holidays still does not provide satisfaction to consumers. Improvement efforts to increase satisfaction with Tourism bus services using the Importance Performance Analysis method in quadrant I (top priority) using SPSS 19 through a cartesius diagram obtained as many as 13 attributes. The most important attributes that are the main priority in repairs to match the expectations of consumers with the value of the suitability level of 78.04, namely the attributes of the availability of clear information marks.